Multiple use management of tropical production forests: How can we move from concept to reality? - Guariguata, Manuel R.; Sist, P.; Nasi, Robert (Elsevier, 2012)
Constraints in making multiple use forest management a more widespread land use type across the tropics still prevail. Technical and managerial capacities usually differ for different forest products, market opportunities and degrees of market knowledge. Local communities or small-scale forest operators face difficulties in adjusting traditional practices to implement official forestry regulations, that are usually drafted with little harmonization of different management objectives and also little consideration of local socio-ecological contexts. Strategies that optimize trade-offs, by nature more complex than trade-offs in single-commodity production systems, have been neglected. Although the available evidence suggests that formal management practices favor specialization over integration, studies that attempted to discern or draw lessons learned seem, to date, limited. This Special Issue is intended to further contribute to the knowledge related to biophysical, institutional, regulatory and socio-economic aspects influencing the design, implementation and effectiveness of multiple use management throughout the forested tropics. A few messages emerge. Although the constraints impeding the implementation of multiple use of forests differ little from the constraints in plans that only include timber, the required trade-offs in the former are expected to be more problematic. Refining the scientific basis for assessing and minimizing trade-offs at different spatial scales is warranted. As important as it may be to establish multiple use objectives from the outset and involve different stakeholders in the planning process, social learning and multi-stakeholder dialogue in the context of adaptive management are needed to maintain these objectives over time, both from the top down and the bottom up. For managers and practitioners to work on multiple forest use in the tropics they must consider spatial aspects in detail, from the stand to the landscape. Finally, moving from “concept to reality” will also require new forestry training and education approaches to keep up with the ever-growing methods for valuing and using tropical forests.